Stereotactic Body Radiotherapy for Primary Prostate Cancer. (13th August 2018) - Kothari, Gargi; Loblaw, Andrew; Tree, Alison C.; van As, Nicholas J.; Moghanaki, Drew; Lo, Simon S.; Ost, Piet; Siva, Shankar
Prostate cancer is the most common non-cutaneous cancer in males. There are a number of options for patients with localized early stage disease, including active surveillance for low-risk disease, surgery, brachytherapy, and external beam radiotherapy. Increasingly, external beam radiotherapy, in the form of dose-escalated and moderately hypofractionated regimens, is being utilized in prostate cancer, with randomized evidence to support their use. Stereotactic body radiotherapy, which is a form of extreme hypofractionation, delivered with high precision and conformality typically over 1 to 5 fractions, offers a more contemporary approach with several advantages including being non-invasive, cost-effective, convenient for patients, and potentially improving patient access. In fact, one study has estimated that if half of the patients currently eligible for conventional fractionated radiotherapy in the United States were treated instead with stereotactic body radiotherapy, this would result in a total cost savings of US250 million per year. There is also a strong radiobiological rationale to support its use, with prostate cancer believed to have a low α/β ratio and therefore being preferentially sensitive to larger fraction sizes. To date, there are no published randomized trials reporting on the comparative efficacy of stereotactic body radiotherapy compared to alternative treatment modalities, although multiple randomized trials are currently accruing. Yet, early results from the randomized phase III study of HYPOfractionated RadioTherapy of intermediate risk localized Prostate Cancer (HYPO-RT-PC) trial, as well as multiple single-arm phase I/II trials, indicate low rates of late adverse effects with this approach. In patients with low- to intermediate-risk disease, excellent biochemical relapse-free survival outcomes have been reported, albeit with relatively short median follow-up times. These promising early results, coupled with the enormous potential cost savings and implications for resource availability, suggest that stereotactic body radiotherapy will take center stage in the treatment of prostate cancer in the years to come.